Glucocorticoids for acute urticaria: study protocol for a double-blind non-inferiority randomised controlled trial. Issue 8 (21st August 2019) - Javaud, Nicolas; Soria, Angele; Maignan, Maxime; Martin, Ludovic; Descamps, Vincent; Fain, Olivier; Bouillet, Laurence; Berard, Frederic; Tazarourte, Karim; Roy, Pierre-Marie; Fontaine, Jean-Paul; Bagot, Martine; et al.
Abstract : Introduction: This study protocol describes a trial designed to investigate whether antihistamine alone in patients with acute urticaria does not increase the 7-day Urticaria Activity Score (UAS7) in comparison with an association of antihistamine and glucocorticoids and reduces short-term relapses and chronic-induced urticaria. Methods and analysis: This is a prospective, double-blind, parallel-group, multicentre non-inferiority randomised controlled trial. Two-hundred and forty patients with acute urticaria admitted to emergency department will be randomised in a 1:1 ratio to receive levocetirizine or an association of levocetirizine and prednisone. Randomisation will be stratified by centre. The primary outcome will be the UAS7 at day 7. The secondary outcomes will encompass recurrence of hives and/or itch at day 7; occurrence of spontaneous hives or itch for >6 weeks; patients with angioedema at day 7, and 2, 6, 12 and 24 weeks; new emergency visits for acute urticaria recurrences at days 7 and 14, and 3 months; Dermatology Life Quality Index at days 7 and 14, and 3 and 6 months; and Chronic Urticaria Quality of Life Questionnaire at 6 weeks. Ethics and dissemination: The protocol has been approved by the Comité de Protection des Personnes Sud-Méditerranée II and will be carried out in accordance with the Declaration of Helsinki and Good Clinical Practice guidelines. A steering committee will oversee the progress of the study. Findings will be disseminated through national and international scientific conferences and publication in peer-reviewed journals. Trial registration number: NCT03545464